Discourse Markers Used in EFL Teacher Talk: A Pragmatic Perspective - Endang Susilowati; Zaenul Wafa (Journalistics: Journal of English Teaching and Applied Linguistics, 2023)
Discourse markers (DMs) play a pivotal role in teacher talk since they not only maintain the classroom interaction but also promote the learning efficiency. This article reports on a study aimed at investigating and examining features and functions of discourse markers used by an EFL teacher. This is a descriptive qualitative study within the frame of pragmatics. The data were derived from audio-video recordings gathered through direct observation. The audio-video recordings were transcribed and analyzed afterwards. In analyzing the data, Brinton’s (2008) framework of DM features was employed to figure out the DM features and the taxonomy of pragmatic functions of DMs proposed by Fung and Carter (2007) was used to examine the functions of DMs. This study spotlights two major findings. Firstly, the discourse markers found are in the form of adverbs, conjunctions, lexical phrases, and fillers, with the five most frequent DMs used are ‘OK’, ‘so’, ‘and then’, ‘now’, ‘and ‘and’. Secondly, the discourse markers perform pragmatic functions, namely interpersonal function (checking progress, partitioning information, replaying to elicitors, seeking affirmation, and signifying acknowledgement), referential function (marking results or consequences), structural function (opening the topic/subject or adjusting the lecture mode, maintaining the students’ attention, and smoothing shifts between activities), and cognitive function (denoting the thinking process). In short, the findings of this study might help to boost awareness of the pragmatic discourse markers for EFL teachers and learners.